ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SERUPA PISA SISWA DENGAN GAYA BELAJAR VISUAL BERDASARKAN LANGKAH KRULIK-RUDNICK - Muhammad Wildan Fadilah; Sri Subanti; Budi Usodo (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The purpose of this study was to describe the mathematical problem-solving ability of Pisa-like level 1 and level 2 students with a visual learning style based on the Krulik-Rudnick step. This research is a qualitative research conducted at Baki 2 Junior High School in the Odd Semester of the Academic Year 2021/2022. The research subjects were three grade VIII students with visual learning styles selected using purposive sampling technique. Data collection techniques using questionnaires, written test and interviews. Questionnaires are used to determine students’ learning styles, meanwhile the written test and interviews were used to determine students' problem-solving abilities. Method triangulation is used to measure the validity of the data between the written test and interviews. The data obtained is then analyzed with the stages of data reduction, data presentation, and drawing conclusions. The results show that at level 1, students can fulfill the indicators at all stages of the Krulik-Rudnick step. While at level 2, students can only fulfill the indicators at the Read and Think and Explore and Plan stages.